(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2016)
This paper addresses, from a legal perspective, the phenomenon of sustainable mobility in Madrid by examining the different actions developed in terms of mobility, with the ultimate purpose of reducing the environmental impact of urban traffic. For that it is necessary to unravel its meaning, scope, and legal consequences in accordance with national, regional and local regulatory.